Metagenomic next-generation sequencing facilitates precision treatment and prognostic improvement in pulmonary cryptococcosis - Xu, Yapeng; Miao, Jingxuan; Chen, Jing; Ye, Liqun; Yang, Kangli; Wang, Hongmin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe early diagnosis of pulmonary cryptococcosis (PC) remains challenging due to the low sensitivity and prolonged turnaround time of conventional diagnostic methods. Despite the broad-spectrum pathogen detection capability of metagenomic next-generation sequencing (mNGS), its clinical utility in the diagnosis and therapeutic management of pulmonary cryptococcosis remains underexplored.MethodsIn this retrospective study, 31 patients diagnosed with Cryptococcus infection through mNGS at The First Affiliated Hospital of Zhengzhou University between July 2023 to March 2025 were included. data on clinical characteristics, treatment regimens, and patient prognosis were systematically collected.ResultsCompared to conventional pathogen detection methods, mNGS demonstrated superior sensitivity, shorter turnaround time (1.00 d vs. 4.50 d, p = 0.002), and significantly reduced interval from admission to clinical decision-making (3.50 d vs. 9.00 d, p = 0.002). Among 31 patients with mNGS-identified cryptococcal infection, only 12 underwent fungal culture, with merely 1 case yielding positive results (positivity rate: 8.33%). Antimicrobial therapy was optimized for all patients based on mNGS findings. During post-discharge follow-up of 27 cases, 1 patient experienced disease recurrence, 1 died from tumor metastasis, and 1 was lost to follow-up.ConclusionOur retrospective analysis revealed that mNGS facilitated treatment optimization, improved clinical outcomes, and provided crucial evidence supporting the precision management of pulmonary cryptococcosis.